PENGARUH INFLASI, TINGKAT SUKU BUNGA DAN KURS TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Famy, Rivaldo; Efriyenti, Dian (LPPM Universitas Putera Batam, 2020)
The higher the stock price, the financial condition of the company will look more stable and stronger, while when the stock price of a company decreases, the financial condition of the company will look unstable and weaker. The purpose of this study is to investigate how significant the influence of inflation, interest rates and exchange rates on stock prices on the Indonesia Stock Exchange. The population taken from industrial and chemical manufacturing companies in the 2015-2019 period was 74 companies. The sample collection technique uses the Purposive Sampling method. The sample used in this study was 18 companies. The results of the study using the t test showed that partially inflation positively did not have a significant effect on stock prices while interest rates negatively and exchange rates positively did have a significant effect on stock price and using the f test showed that simultaneously inflation, interest rates and exchange rates positively did have a significant effect on prices stock